2016
DOI: 10.1016/j.tecto.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fabrics in the Bjerkreim Sokndal Layered Intrusion, Rogaland, southern Norway: Mineral sources and geological significance

Abstract: Magnetic anisotropy can provide important information about mineral fabrics, and thus magmatic processes, particularly when it is known how multiple mineral species contribute to the anisotropy. It may also affect the direction of induced or remanent magnetization, with important consequences for paleomagnetic studies or the interpretation of magnetic anomalies. Here, we aim at describing the magnetic fabrics in the Bjerkreim Sokndal Layered Intrusion and identifying their carriers.Anisotropies of magnetic sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 117 publications
(136 reference statements)
0
15
0
Order By: Relevance
“…The orientation of the site mean principal susceptibility axes is generally similar in sites that are located close together but changes in accordance with the trend of the layers. Overall, the minimum susceptibility is approximately perpendicular to the foliation and magmatic layering, as has been found on a subset of specimens previously studied [ Biedermann et al ., ; Paludan et al ., ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The orientation of the site mean principal susceptibility axes is generally similar in sites that are located close together but changes in accordance with the trend of the layers. Overall, the minimum susceptibility is approximately perpendicular to the foliation and magmatic layering, as has been found on a subset of specimens previously studied [ Biedermann et al ., ; Paludan et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Newly collected specimens are labeled BK2015_xx, and specimens available from earlier studies are named BKxx. The magnetic fabrics of some of these specimens have been described previously [ Biedermann et al ., ]. In total, 371 specimens from 46 sites, including 265 new specimens from 95 drill cores in 29 sites, and 106 existing specimens from 16 drill cores and 13 oriented blocks in 17 sites, were selected for this study (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface samples have been collected from various locations in the MCU IVe′ layer, and additional samples from the MCU IVe′ layer and other layers of the intrusion were available from previous studies (Figure ). A detailed description of sampling and sample preparation is given in Brown and McEnroe () and Biedermann et al (). Throughout this study, magnetic property results will be shown for two sets of samples: in total, 570 samples from 101 sites have been used, including samples from layers IAa, IBa, IBc, IBe, IIc, IIIa, IIIc, IIId, IIIe, IIIf, IVa, IVb, IVc, IVd, IVe, IVe′, IVf, and mangerite, and 310 of these from 39 sites originate within the MCU IVe′ layer.…”
Section: Bjerkreim Sokndal (Bks) Case Studymentioning
confidence: 99%